Urgency of Evaluation of Sekolah Penggerak Program Through the Cipp Model (Context, Input, Process, Product): A Critical Study - Hasudungan, Anju Nofarof; Suboh, Amerruddin Shah; Nababan, Surya Aymanda (Medan Resource Center, 2024)
This research aims to recommend the urgency of evaluating the Sekolah Penggerak program in high schools using the CIPP (Context, Input, Process and Product) model. Sekolah Penggerak are schools selected and selected by the Ministry of Education and Culture, Technology Research of the Republic of Indonesia to implement the Merdeka curriculum. The Sekolah Penggerak can also be assumed to be a derivative product of the Merdeka curriculum which replaced the 2013 curriculum and the emergency curriculum. This research uses qualitative research. Qualitative research is research that aims to understand the conditions of a context by leading to a detailed and in-depth picture of what is happening according to what is happening. The results of the research show that the Ministry of Education and Culture, under the leadership of Nadiem Anwar Makarim, launched a superior program, namely, Sekolah Penggerak which is believed to be a necessity and a way to improve and improve the quality of education in schools. The Sekolah Penggerak program that has been implemented should have undergone a comprehensive evaluation and this is an important need. Critically, programs that have been created and implemented in a lively manner and using funds from public money which also have direct contact with the people should be evaluated to determine their usefulness in the field of education. Therefore, the author recommends the CIPP model as an evaluation model used for the Sekolah Penggerak program which is the current flagship program of the Ministry of Education and Culture.